Aberrant blood brain barrier dynamics in cerebral small vessel disease - a review of associations, pathomechanisms and therapeutic potentials - Zul Ramli, Sayyidah Maryamul Azra’; Abdul Hamid, Hafizah; Che Mohd Nassir, Che Mohd Nasril; A Rahaman, Siti Nurulnabila; Mehat, Muhammad Zulfadli; Kumar, Jaya; Lee, Si-Yuen; Mustapha, Muzaimi (OAE Publishing Inc., 2024)
This review explores the pivotal role of the blood-brain barrier (BBB) in maintaining central nervous system (CNS) homeostasis and its dynamic involvement in the pathogenesis of cerebral small vessel disease (CSVD), i.e., the major precursor of age-related neurodegenerative diseases such as vascular dementia and Alzheimer’s disease. It underscores the BBB as a critical physiological boundary that regulates the exchange between the bloodstream and the cerebral milieu through a complex and dynamic interface composed of endothelial cells, astrocyte endfeet, and pericytes. The integrity of this barrier is paramount for neural function, shielding the brain from toxicants and pathogens while facilitating the transport of essential nutrients. Nevertheless, BBB dysfunction is recognized as a lead in the pathogenesis of neurodegeneration including CSVD, emphasizing the need for focused research on maintaining or restoring BBB function. This review highlights recent advancements in our understanding of BBB dynamics in both health and disease states, its involvement in CSVD pathomechanisms, and the challenges and future directions of translational research and emerging technologies. The review advocates for a multidisciplinary approach to uncover the complexity of BBB dysfunction in CSVD, as well as insights into potential therapeutic targets aimed at preserving BBB integrity, thereby minimizing its impact given the notable world’s aging demographics.